Apert syndrome: Analysis of associated brain malformations and conformational changes determined by surgical treatment - Yacubian-Fernandes, A. [UNESP]; Palhares Neto, Aristides Augusto [UNESP]; Giglio, A.; Gabarra, Roberto Colichio [UNESP]; Zanini, S.; Portela, L.; Plese, J. P P (Elsevier, 2004)
Apert Syndrome, also called acrocephalosyndactylia type 1, is characterized by craniostenosis with early fusion of sutures of the vault and/ or cranial base, associated to mid-face hypoplasia, symmetric syndactylia of the hands and feet and other systemic malformations. CNS malformations and intracranial hypertension are frequently observed in these patients. Early surgical treatment aims to minimize the deleterious effects of intracranial hypertension. Fronto-orbital advancement, the usual surgical technique, increases the intracranial volume and improves the disposition of encephalic structures previously deformed by a short skull. This study analyzes CNS alterations revealed by magnetic resonance in 18 patients presenting Apert Syndrome, and the conformational alterations in the encephalic structures after surgical treatment. The patients' age in February 2001 ranged from 14 to 322 months (m=107). Image study included brain magnetic resonance showing ventricular enlargement in five cases (27.8%), corpus callosum hypoplasia in five cases (27.8%), septum pellucidum hypoplasia in five cases (27.8%), cavum vergae in two cases (11.1%) and, arachnoid cyst in the posterior fossa in two cases (11.1%). Absence of CNS alterations was noted in 44.4% of cases. A corpus callosum morphologic index was established by dividing its height by its length, which revealed values that ranged from 0.4409 to 1.0237. The values of this index were correlated to the occurrence or absence of surgical treatment (p=0.012; t=2.83). Data analysis allowed the conclusion that the corpus callosum morphologic measure quantified the conformational alterations of the cerebral structures determined by the surgical treatment.
Keywords: Acrocephalosyndactylia type I; Apert Syndrome; Brain anomalies; Corpus callosum; MR imaging; acrocephalosyndactyly; brain arachnoid cyst; brain malformation; brain tomography; brain ventricle dilatation; clinical article; controlled study; corpus callosum; correlation analysis; data analysis; disease association; female; height; human; male; neuroimaging; neurosurgery; newborn; nuclear magnetic resonance imaging; septum pellucidum; skull; Acrocephalosyndactylia; Adolescent; Adult; Brain Diseases; Central Nervous System; Child; Child, Preschool; Female; Humans; Infant; Magnetic Resonance Imaging; Male; Molecular Conformation; Surgical Procedures, Elective; Treatment Outcome